TEKANAN KETAATAN DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT - Kusumawaty, Mia; Krisnahari, Kurnia (Universitas Muhammadiyah Palembang, 2022)
This research was conducted to answer the existing problem, namely how much influence obedience pressure and auditor experience have on audit judgment. The aim is to determine the effect of obedience pressure and auditor experience on audit judgment. This research uses associative and descriptive research. The place of research was carried out at the Public Accounting Firm (KAP) in Palembang City. The variables used are obedience pressure, auditor experience, and audit judgment. The data used is primary data. Data collection techniques used in this study were questionnaires and interviews. The data analysis technique used in this research is descriptive statistics and inferential statistics. Inferential statistical analysis consisted of classical assumption test, multiple linear regression analysis, coefficient of determination, and hypothesis testing (t test) assisted by Statistical Program For Special Science (SPSS). The results showed that obedience pressure and auditor experience had a significant effect on audit judgment at KAP in Palembang City.